PENGARUH PENERAPAN AKTIVITAS MENGGAMBAR DAN MERIAS DIRI TERHADAP PENURUNAN TANDA DAN GEJALA PADA PASIEN HARGA DIRI RENDAH DI WILAYAH KERJA UPTD PKM KONCARA - Grace Evelyn,; Dina Hartini ,; Dini, Dini (Journal of Innovation Research and Knowledge, 2025)
Low self-esteem is a self-concept disorder that often occurs in patients with mental disorders and psychosocial problems. This condition is characterized by feelings of worthlessness, lack of self-confidence, and withdrawal from the social environment. Non-pharmacological efforts that can help improve self-esteem are through drawing and makeup activities, which can stimulate self-expression and strengthen a positive body image. To determine the effect of implementing drawing and makeup activities on reducing signs and symptoms in patients with low self-esteem in the work area of ​​​​the UPTD PKM Koncara. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 20 respondents who were selected purposively. Data collection was carried out using an observation sheet for signs and symptoms of low self-esteem based on the SDKI (2019) guidelines. The intervention was carried out for two days: the first day was expressive drawing activities, the second day was makeup activities. Data analysis used the Wilcoxon Signed Rank Test with a significance level of α = 0.05. Results The average score of signs and symptoms of low self-esteem before the intervention was 15.20, and after the intervention decreased to 8.30. The Wilcoxon test results showed a p-value of 0.000 (p < 0.05), indicating a significant effect of drawing and makeup activities on reducing signs and symptoms of low self-esteem. Conclusion: Drawing and makeup activities effectively reduce signs and symptoms of low self-esteem. This therapy can be used as an alternative nursing intervention in group activity therapy programs in community health facilities.